Supplemental oxygen did not significantly affect two-year mortality in patients at-risk for cardiovascular complications undergoing moderate- to high-risk abdominal surgery–A follow-up analysis of a prospective randomized clinical trial - Taschner, Alexander; Fleischmann, Edith; Kabon, Barbara; Falkner von Sonnenburg, Markus; Adamowitsch, Nikolas; Horvath, Katharina; Christian, Thomas; Emler, David; Fraunschiel, Melanie; Graf, Alexandra; Reiterer, Christian (Frontiers in Anesthesiology, 2023)
Background: In relatively healthy middle-aged patients, recent studies have shown that supplemental oxygen did not significantly increase one-year mortality after noncardiac surgery. If supplemental oxygen influences long-term mortality, specifically in elderly patients with cardiovascular risk-factors, remains unknown. Thus, we evaluated the effect of supplemental oxygen on two-year mortality in patients with cardiovascular risk factors undergoing moderate- to high-risk major abdominal surgery. Methods: This is a follow-up study of a prospective, randomized, double-blinded, clinical trial. 258 patients, who were at least 45 years of age and at-risk for cardiovascular complications were randomly assigned to receive 80% versus 30% oxygen during surgery and for the first two postoperative hours. Vital status was obtained from all patients two years after surgery using the national registry. Preoperative and postoperative maximum concentrations of NT-proBNP, Troponin T (TnT), Copeptin, von Willebrand Factor (vWF), static oxidation-reduction potential (sORP) and oxidation-reduction potential capacity (cORP) were tested for association with two-year mortality. Results: The median age of patients was 74 years (25th percentile – 75th percentile 70-78 years). 25.8% (95% CI: 17.3% to 32.4%) of patients in the 80% oxygen group and 22.3% (95% CI: 14.8% to 29.1%) in the 30% oxygen group died within two years after surgery. No significant difference in two-year mortality was found between patients, who received 80% oxygen concentration, versus patients, who received 30% oxygen concentration (estimated hazard ratio 1.145; 95% CI 0.693 to 1.893; p = 0.597). Preoperative Copeptin concentrations and postoperative maximum vWF activity were significantly associated with two-year mortality (p < 0.001). Conclusion: Our results are consistent with previous studies, that showed that supplemental oxygen did not increase long-term mortality. Therefore, it is becoming more evident that supplemental oxygen may not have a significant effect on long-term outcome in patients undergoing major abdominal surgery.